1990
DOI: 10.3758/bf03197091
|View full text |Cite
|
Sign up to set email alerts
|

The effects of recoding and presentation format on recency and suffix effects

Abstract: The primary linguistic theory of Shand and Klima (1981) hypothesizes that stimuli that cannot be directly processed without recoding are not in the primary linguistic mode of the subject and thus should lead to lesser recency and associated suffix effects. In three experiments, different normal hearing subjects learned to pair American Sign Language (ASL) stimuli, visual "quasivocables" (QVs), word-like letter strings, and auditory QVs with common English words. In the first experiment, the subjects were given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1990
1990
2004
2004

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Lastly, the finding that prolonged visual exposure added to auditory repetition did not change the semantic satiation effects observed with auditory repetition alone suggests that two converging sources of satiation do not produce additive effects. Of course, the encoding of visual stimuli involves the translation of visual patterns into orthographic codes before the latter can activate phonological codes (Manning, Koehler , & Hampton, 1990). Because auditory stimuli have a more direct route to phonological information, it is possible that they provided the phonological codes for the visually presented stimuli, and thus reduced the processing of the latter in our experiment.…”
Section: Resultsmentioning
confidence: 97%
“…Lastly, the finding that prolonged visual exposure added to auditory repetition did not change the semantic satiation effects observed with auditory repetition alone suggests that two converging sources of satiation do not produce additive effects. Of course, the encoding of visual stimuli involves the translation of visual patterns into orthographic codes before the latter can activate phonological codes (Manning, Koehler , & Hampton, 1990). Because auditory stimuli have a more direct route to phonological information, it is possible that they provided the phonological codes for the visually presented stimuli, and thus reduced the processing of the latter in our experiment.…”
Section: Resultsmentioning
confidence: 97%
“…One possible explanation is that the elderly show a relative deficit in recoding stimuli. A considerable body of research has suggested that visual stimuli are processed in such a way that they are recoded (see Manning, Koehler, & Hampton [1990] for a discussion of different types of recoding) into a representation which contains auditory components, while auditory stimuli produce representations more similar to the physical signal. Support for this view comes from classic work such as that of Conrad (1964), which shows that normal adults frequently make auditory confusion errors with visually-presented stimuli while the reverse confusions may be relatively rare (see, however, Manning, 1977).…”
mentioning
confidence: 99%
“…Although the modality effect is extremely strong and consistent (see, e .g ., Frankish, 1989;Frick, 1988;Glenberg & Swanson, 1986 ;Manning et al , 1990;Nairne, 1988;Penney, 1989), no adequate explanation exists for it or for the similar effects with lip-read stimuli.…”
mentioning
confidence: 99%
“…Past research has consistently shown that the recency effect is greater for auditorily as opposed to visually presented stimuli (e.g ., Frick , 1988;Glenberg & Swanson, 1986;Manning, Koehler , & Hampton, 1990 ;Nairne , 1988) , particularly in serial recall. In fact , auditory stimuli tend to produce Ushaped serial position curves in serial recall tasks , whereas visual stimuli either produce J-shaped curves, with a minimal recency effect, or no recency effect at all (Greene, 1987;Manning & Schreier, 1988;Penney, 1989).…”
mentioning
confidence: 99%